Mobilizing Ordinary People for the Sake of the Environment: Challenges of Urban Activists within Clientelistic Conditions in Lebanon - Lyne Jabri (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This article is about urban and environmental activism in a place driven by market economy and clientelism; two conditions that, when conjoined, make it very hard to protect the environment from encroachment by the forces of urbanization and industry. The context is Lebanon, where many urban and environmental initiatives have been sprouting in the last decade. In this difficult context, what strategies can urban and environmental activists use to make a case for the stewardship of the environment? What opportunities might they use to mobilize ordinary people, who are often relegated to being the clientele of political patrons, to mobilize collective action over environmental issues? In fact, mobilizing people is the only way to go when political leaders and public officials turn a blind eye. The article concentrates on the experience of Lil-Madina Initiative, an activist group in the city of Saida that has been trying to make a case for ecological rejuvenation in the city since the formation of the collective in 2013. By backing the experience of Lil-Madina Initiative with other activists’ experiences from Lebanon, the article demonstrates that ordinary people are often mobilized only once their perceived personal interests are at stake, or, exceptionally, within extra-ordinary conditions such as an uprising. The article concludes by providing the example of a community garden in Greater Saida, to demonstrate that ordinary people may be mobilized when the subject of contention — in this case the agricultural lands of Saida — becomes part of their daily lives and routines.